Validity and reliability of healthy food knowledge and healthy food preferences scale for preschool children - Roba, Aklilu Abrham; Başdaş, Öznur (Frontiers in Pediatrics, 2025)
IntroductionEarly childhood nutrition plays a critical role in shaping lifelong health outcomes, yet preschool children in low- and middle-income countries often have poor dietary habits and limited knowledge of healthy foods. This study aimed to validate and assess the reliability of the 9-item Healthy Food Knowledge (HFK_PS) and Healthy Food Preference (HFP_PS) scales, ensuring cultural relevance for measuring food knowledge and preferences among Ethiopian preschool children aged 3–7 years.MethodsA cross-sectional design was employed, involving 319 preschoolers from five randomly selected 5 kindergarten schools. Data was collected through an interactive photo-based interview with the children. A panel of ten experts assessed content validity, while construct validity was assessed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Reliability was assessed using Cronbach's alpha.ResultsThe EFA identified a two-factor structure for both scales, explaining 50.91% and 50.18% of the variance for HFK_PS and HFP_PS, respectively. CFA confirmed the model fit, with all indices meeting the recommended thresholds. The HFK_PS and HFP_PS scales demonstrated good internal consistency, with Cronbach's alpha values of 0.80 and 0.78, respectively. Older children and those in higher grades had significantly greater food knowledge (p < 0.001), and food preferences also improved with grade level (p < 0.05). However, preferences remained stable across age groups (p = 0.928). However, no significant gender differences were found. A positive correlation (r = 0.43, p < 0.001) was found between healthy food knowledge and preferences, suggesting that increased knowledge is associated with healthier preferences.ConclusionsThe validated scales can be instrumental in evaluating preschoolers' dietary knowledge and preferences in Ethiopia. Future studies should focus on implementing these scales in nutrition education programs to assess their effectiveness in fostering long-term healthy eating habits among young children.